Crocin alleviates the local paw edema induced by histamine in rats - Tamaddonfard, Esmaeal (Mashhad University of Medical Sciences, 2012)
Objective: Crocin, as an active constituent of saffron, has many biological functions including antioxidant and anti-inflammatory activities. The present study was aimed to investigate the effects of crocin and chlorpheniramine on local edema induced by histamine. Materials and Methods: Local edema was induced by subcutaneous injection of histamine (100 μl, 0.1%) in ventral surface of right hind paw. The thickness of paw was measured at 1 h before and 1, 2, 3 h after injection of histamine, using a fine caliper. The number of neutrophils in paw tissue sections was counted 3 h after intraplantar injection of histamine. Results: Intraperitoneal injection of crocin at doses of 100 and 200 mg/kg and chlorpheniramine at a dose of 10 mg/kg significantly (p<0.05) decreased both paw thickness and infiltration of neutrophils in paw tissues. In a combined treatment, intraperitoneal injection of an effective dose of crocin (100 mg/kg) with an ineffective dose of chlorpheniramine (2.5 mg/kg) produced a more documented response in comparison with crocin (100 mg/kg) and chlorpheniramine (2.5 mg/kg) used alone. Conclusion: The results suggested that both crocin and chlorpheniramine suppressed histamine-induced local paw edema. Moreover, histamine H(1) receptors function may be affected by crocin.